A Multicenter Study of Bacterial Vaginosis in Women With or at Risk for Human Immunodeficiency Virus Infection - Dora Warren; Robert S. Klein; Jack Sobel; Burney Kieke; William Brown; Paula Schuman; Jean Anderson; Susan Cu-Uvin; Kenneth Mayer; Denise J. Jamieson; Scott Holmberg; Ann Duerr (Hindawi Limited, 2001)
Background: Bacterial vaginosis is a common gynecologic infection that has been associated with a variety of gynecologic and obstetric complications, including pelvic inflammatory disease, postabortal infection and premature delivery. Recent studies suggest that bacterial vaginosis may increase a woman's risk for human immunodeficiency virus (HIV). We undertook this study to assess whether the prevalence and characteristics of bacterial vaginosis differed according to HIV status in high-risk US women.